2012
DOI: 10.1111/j.1439-0507.2012.02169.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the prevalence of invasive fungal infections from an analysis of annual records of autopsy cases of Toho University

Abstract: Clinical diagnosis of invasive fungal infections (IFIs) is sometimes difficult, and obtaining an accurate assessment of trends concerning the prevalence of IFIs is a challenge. The aim of this study was to determine trends in the prevalence of IFIs from an autopsy survey. The retrospective review of autopsy records stored in Toho University was performed on all documented cases with fungal infection from 1955 to 2006. A total of 411 cases of IFIs were detected among 10 297 autopsies. The prevalence of candidia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 27 publications
(36 reference statements)
0
17
0
2
Order By: Relevance
“…İnvazif küf infeksiyonlarının en sık nedeni Aspergillus cinsinde yer alan mantarlardır (22) . Bunlar invazif infeksiyonlardan alerjik sendromlara kadar değişen klinik tablolara neden olmaktadır (11,12) .…”
Section: Discussionunclassified
“…İnvazif küf infeksiyonlarının en sık nedeni Aspergillus cinsinde yer alan mantarlardır (22) . Bunlar invazif infeksiyonlardan alerjik sendromlara kadar değişen klinik tablolara neden olmaktadır (11,12) .…”
Section: Discussionunclassified
“…The presence of fungal infections was confirmed through histopathological analysis of all samples by 3 expert pathologists who reexamined the samples using hematoxylin and eosin staining and Grocott's methenamine silver (GMS) staining. Since it has been previously reported that the lung was the most common organ involved irrespective of major fungal species, the lung was adopted as the representative organ of IFI (7). Tissues obtained from the autopsies were fixed in 15z unbuffered formalin before being paraffin embedded and stored at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of candidiasis decreased from 3.6% (1981-93) to 2.0% (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006), while that of aspergillosis increased throughout the 52-year period and reached 2.0%. 3 Additionally, similar to the development of antibiotic resistance, the use of broad-spectrum antifungal agents such as voriconazole has led to the emergence of IFI caused by the mucormycetes class of fungi. 4 In a case-control study involving 14 leukemic and 13 HSCT patients, voriconazole prophylaxis was identified as an independent risk factor, increasing the risk for invasive mucormycosis by more than 10-fold.…”
Section: Epidemiological Facts In Invasive Fungal Infections -What Hamentioning
confidence: 99%